Multi-method strategies for provenance determination of coarse-grained igneous rocks: Non-destructive, portable, and quantitative approaches - Bongsu Chang; Tae Gun Jo; Young Jae Lee (PLoS ONE, 2025)
Determining the provenance of stones used in cultural heritage artifacts requires interdisciplinary research that integrates archaeology, geology, and analytical science. In this study, we determined the provenance of the source rock for a Bodhisattva stone sculpture from an abandoned temple site in Haman, South Korea. Non-destructive, portable, in-situ multi-analytical methods were used to quantitatively analyze coarse-grained igneous rocks, incorporating macroscopic observations, portable X-ray fluorescence (pXRF), and magnetic susceptibility measurements. Calibration with matrix-matched in-house rock standards and quality checks ensured the reliability of pXRF data for major, minor, and several trace elements, supporting accurate provenance identification. Analysis of spatial variations in chemical composition revealed two distinct geochemical trends across plutonic rock bodies spanning tens of kilometers, providing a key strategy to narrowing down the source area. Our findings present a robust methodology with broad applicability for investigating plutonic rock provenance.